Pomiędzy przekleństwem a intelektualną rozmową, czyli o języku bohaterów przebojów wydawniczych w Niemczech (Conversatoria Linguistica, 2019)
Every period has its own heroes and its own great bestsellers. In this article I will refer to two extremely popular works in their own times. The first is one of the stories from the Magda Trott’s series for girls and young women with the flag character – Pucki, entitled “New Pucki’s Pranks” dating back to 1930s, the second one is a Helene Hegemann novel published in 2010 by Ullstein under the title Axolotl Roadkill. The young women discourse presented on the pages of these two novels cannot be more distinct at first sight. And yet despite distinct differences it includes similar elements. For youth is, almost always, the family problems, the time for first loves or